2010
DOI: 10.2353/ajpath.2010.091252
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction and Circulating Microparticles from Patients with Obstructive Sleep Apnea

Abstract: Endothelial dysfunction is involved in vascular complications of obstructive sleep apnea (OSA). In this study, circulating microparticles (MPs) from patients with OSA-induced nocturnal desaturations were characterized and their effects on endothelial function were evaluated. Two age-matched groups of patients undergoing polysomnography for OSA were compared: 35 desaturators with a 3% oxyhemoglobin desaturation index (ODI) > or = 10 events per hour of sleep and 27 nondesaturators with ODI <10 events per hour. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 35 publications
9
92
0
Order By: Relevance
“…In the current meta-analysis, ICAM was found to be higher in OSA patients than the control group. In many studies, ICAM-1 (intercellular adhesion molecule 1) was found to be higher in patients with OSAS 60,82,83 and its level correlated with OSAS severity, particularly with nocturnal hypoxemia.…”
Section: Intracellular Adhesion Moleculesmentioning
confidence: 99%
“…In the current meta-analysis, ICAM was found to be higher in OSA patients than the control group. In many studies, ICAM-1 (intercellular adhesion molecule 1) was found to be higher in patients with OSAS 60,82,83 and its level correlated with OSAS severity, particularly with nocturnal hypoxemia.…”
Section: Intracellular Adhesion Moleculesmentioning
confidence: 99%
“…1 Meanwhile, hypoxia can lead to increased blood pressure and a weakened response of the vascular system to vasodilatation factors, resulting in dysfunction of blood vessel and tissue selfregulation 2 and vascular endothelial disorders. 3 Previous studies have suggested that OSAS acts as an independent risk factor and leads to hypertension, heart disease, and stroke through the mechanisms described above. [4][5][6] OSAS can have a similar effect on the eye.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Korzh et al [42] stated that the levels of VCAM-1, E-selectin, P-selectin, CRP, WBC count were higher in OSA patients than in control subjects [42]. Similarly, several studies found direct significant relationship between adhesive molecules and severity of OSA measured by ODI and AHI [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%